Penerapan Green Human Resource Management (GHRM) dan Dampaknya terhadap Kinerja Aparatur Sipil Negara di Pemerintah Kota Medan - Jupianus Sitepu; Rahel Br Sukatendel; Rita Vinolia Aruan (LP3M Universitas Putra Bangsa, 2026)
Growing awareness of environmental issues has encouraged public sector organizations to integrate sustainability principles into human resource management. This study aims to analyze the implementation of Green Human Resource Management (GHRM) and its impact on the performance of Indonesia’s State Civil Apparatus (ASN) within the Medan City Government. The study employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and document analysis across several regional government agencies within the Medan City Government. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing. The findings indicate that GHRM has been implemented through the digitalization of personnel administration, reduced paper consumption, environmental awareness training, and the adoption of an environmentally friendly workplace culture. These practices have contributed to improvements in work efficiency, employee discipline, public service innovation, and ASN productivity. However, several challenges remain, including employees’ limited understanding of GHRM, budget constraints, and the absence of well-developed policies specifically governing GHRM practices in the public sector. This study recommends strengthening relevant policies and implementing continuous training programs to support the transformation toward a green bureaucracy within the Medan City Government